1999
DOI: 10.1097/00005344-199908000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan Enhances Cardiac Performance After Cardiopulmonary Bypass: A Prospective, Randomized Placebo-Controlled Trial

Abstract: Levosimendan is a new myofilament calcium (Ca2+) sensitizer that increases myocardial contractility by stabilizing the Ca2+-bound conformation of troponin C. We tested the hypothesis that levosimendan enhances cardiac performance after cardiopulmonary bypass (CPB). Anesthesia was induced and maintained with midazolam, sufentanil, and vecuronium in 18 patients randomly assigned to receive levosimendan (18 or 36 microg/kg loading dose and 0.2 or 0.3 microg/kg/min infusion, respectively) or placebo 15 min before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(81 citation statements)
references
References 28 publications
7
59
1
9
Order By: Relevance
“…It has a short half-life of about an hour but is metabolized to an active metabolite, OR-1896, with an elimination half-life of 70-80 h. Levosimendan is currently used for treatment of decompensated heart failure caused by chronic cardiac failure, acute myocardial infarction, and post-cardiac bypass surgery [3,9]. Several studies have demonstrated the benefits of levosimendan in patients after cardiopulmonary bypass to enhance their cardiac performance [10]. Levosimendan is also a vascular smooth muscle ATP-potassium channels agonist, which reduces after load and peripheral vascular resistance [11].…”
Section: Discussionmentioning
confidence: 99%
“…It has a short half-life of about an hour but is metabolized to an active metabolite, OR-1896, with an elimination half-life of 70-80 h. Levosimendan is currently used for treatment of decompensated heart failure caused by chronic cardiac failure, acute myocardial infarction, and post-cardiac bypass surgery [3,9]. Several studies have demonstrated the benefits of levosimendan in patients after cardiopulmonary bypass to enhance their cardiac performance [10]. Levosimendan is also a vascular smooth muscle ATP-potassium channels agonist, which reduces after load and peripheral vascular resistance [11].…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies after resuscitation from cardiac arrest 418,419,[421][422][423][424] and post-cardiac surgical experience in children 352 and adults, [425][426][427][428] hemodynamic improvement was associated with administration of selected vasoactive agents. Each drug and dose must be tailored to the patient because clinical response is variable.…”
Section: Drugs Used To Maintain Cardiac Output (Table 2)mentioning
confidence: 99%
“…In a small randomized study, Nijhawan and colleagues 27 compared the hemodynamic effects of 2 doses of levosimendan (0.2 or 0.3 g/kg per min infused for 6 hours) with that of placebo after cardiopulmonary bypass. At 15 minutes after the end of cardiopulmonary bypass, levosimendan increased cardiac output and reduced systemic vascular resistance without hypotension or tachycardia.…”
mentioning
confidence: 99%